PENGARUH BAKTERI ASAM LAKTAT SEBAGAI STARTER PADA PROSES ENSILASE - Sri Sumarsih (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
The aim of the research was to evaluate the effect of addition starter Lactic Acid Bacteria (LAB) on organoleptic quality of napier grass silage. The completely randomized design was been used on this research with 3 treaments and 5 replications. The treatments were different level LAB ( 0 %, 1 % dan 2% v/w). The parameters were physical organoleptic quality silage (pH, color, odor, texture, and molds). The results showed that physical organoleptic quality of napier grass silage with a starter BAL organoleptic significant (p <0.05) better than without the addition of starter BAL. The conclusion was the use of starter lactic acid bacteria on ensilage process produces physical organoleptic qualities of good silage.